2018
DOI: 10.1155/2018/3476476
|View full text |Cite
|
Sign up to set email alerts
|

In VivoMRI of Functionalized Iron Oxide Nanoparticles for Brain Inflammation

Abstract: Microglia are intrinsic components of the brain immune system and are activated in many central nervous system disorders. The ability to noninvasively image these cells would provide valuable information for both research and clinical applications. Today, most imaging probes for activated microglia are mainly designed for positron emission tomography (PET) and target translocator proteins that also reside on other cerebral cells. The PET images obtained are not specific for microglia-driven inflammation. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 53 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…Due to their cysteine-rich binding sites, SR-As recognize polyanionic ligands through electrostatic interactions. This includes dimercaptosuccinic acid (DMSA) [ 152 ], carboxy-dextran [ 147 ], and dextran sulfate [ 149 ]. Novel PEG-coated IONs conjugated with thymidine-rich DNA oligonucleotides were recently developed for macrophage labeling and atherosclerotic plaque detection in vivo by exploiting their enhanced recognition by SR-As [ 146 ].…”
Section: Enhancing Ion Internalizationmentioning
confidence: 99%
“…Due to their cysteine-rich binding sites, SR-As recognize polyanionic ligands through electrostatic interactions. This includes dimercaptosuccinic acid (DMSA) [ 152 ], carboxy-dextran [ 147 ], and dextran sulfate [ 149 ]. Novel PEG-coated IONs conjugated with thymidine-rich DNA oligonucleotides were recently developed for macrophage labeling and atherosclerotic plaque detection in vivo by exploiting their enhanced recognition by SR-As [ 146 ].…”
Section: Enhancing Ion Internalizationmentioning
confidence: 99%
“…In our study, we found satisfactory viability values using a 4-h labeling time (99.3%, 99.6% and 98.6% for the respective M-SPION concentrations of 10, 30 and 50 µg Fe/mL). In studies on granulocyte and leukocyte-labeling with SPIONs, the incubation time was reported to be between 1 and 4 h for labeling [51,54,57,59,61,62,85,86]. For example, in the study of Tang et al [61], an incubation time of 3 h was best for the clinical application of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies employing exogenously labeled granulocytes to analyze infection or inflammation processes have used SPIONs with different strategies [51,54,[57][58][59][60][61][62]. SPIONs, when coupled with near-infrared spectrum fluorophores, enhance pathological assessments due to the sensitivity or specificity of the complementary information provided by the optical imaging modality [63], enabling multimodal imaging [64,65].…”
Section: Introductionmentioning
confidence: 99%
“…With its ability to image during the lifetime of the subject, whether animal or human, MRI can be used in experimental settings to investigate disease progression longitudinally, which can then be correlated with postmortem immunostaining for microglia and monocytes (Neuwelt et al, 2009), in addition to various disease hallmarks (Justicia et al, 2008;Jacobs et al, 2012;Tang et al, 2018;Yi et al, 2019). In a rat model of glioma, tumors were imaged during growth progression while studying the microglial/macrophagic changes visualized using ultrasmall superparamagnetic iron oxides (USPIOs).…”
Section: Mrimentioning
confidence: 99%